Prescription Profile and Clinical Outcomes in Patients with Allergic Rhinitis Treated with Oral Antihistamines or Nasal Corticosteroids - Sánchez,Guillermo (2019)
Abstract Introduction Oral antihistamines and intranasal corticosteroids have been shown to be effective and safe for the treatment of allergic rhinitis; however, the evidence suggests a level of superiority of corticosteroids, so they should be preferred over the former. Objective To know the prescription profile of two second generation antihistamines (cetirizine and levocetirizine) and two nasal corticosteroids (mometasone and furoateciclesonide) in a cohort of patients with allergic rhinitis, and to compare the clinical outcomes obtained. Methods A cohort study was carried including patients with allergic rhinitis treated with cetirizine, levocetirizine, mometasone furoate or ciclesonide. The improvement was evaluated with the total nasal symptoms score (TNSS). This scale yields results between 0 and 12. Zero indicates absence of symptoms. Results A total of 314 patients completed 12 weeks of follow-up. Seventy-five percent were treated with antihistamines, 20% with corticosteroids, and 5% with a combination of the above. The TNSS median for corticosteroid was 2.5 points; for antihistamines, its was 5 points, and for combination, it was 4 points. We found differences between corticosteroids and antihistamines. Conclusion The prescription percentage of second generation oral antihistamines is higher than that of intranasal corticosteroids. However, patients with allergic rhinitis treated with the second option obtained better control of symptoms.